A utilização do aleitamento materno no tratamento da fenilcetonúria - Viviane de Cassia Kanufre (2006)
This study aims to evaluate the use of breast-feeding in the treatment of phenylketonuria (PKU). PKU infants, who were born in term, weight > 2.500 g, with no other associated disease, and to whom breast-feeding was kept as phenylalanine (phe) source, were prospectively studied. The found results were compared with those from other PKU infants(control group), using the same criteria of inclusion, but, in this group, the source of phe was a commercial lacteal formula. Altogether, 35 children from each breast-feeding group and control group were evaluated according to sex and age, concerning breast-feeding suspension. The data were analyzed until the definitive suspension of the breast-feeding or, at most, during 12 months of mixed breast-feeding, after the beginning of the treatment. A babys bottle with the special formula was offered to breast-feeding group, each three hours,containing proteic substitute (free of phe), carbohydrates and lipids. Free demand of mothers milk was offered in the intervals. A special formula in the babys bottle was offered to control group, each three hours, containing, besides the nutrients cited above, a commerciallacteal formula as source of phe. Only in breast-feeding group the duration of the natural breast-feeding and the need of the addition of commercial lacteal formula to the special formula, in order to keep the recommended phe blood levels. The necessary time to the adequacy of phe levels in blood were compared after the beginning of the treatment, using Wilcoxon test. The monthly means of phe levels in blood during the breast-feeding were analyzed. Also, the anthropometric data between the two groups were analyzed and compared through t student test matched, using the score Z > -2 as the limit between the eutrophy and malnutrition. The average duration of breast-feeding was 224.4 + 120,1 days. The commercial lacteal formula adding was necessary in the diet of 24 (68.5%) children from breast-feeding group. The necessary average time to the adequacy of phe levels in blood was 11.4 + 6.6 days and 9.8 + 3.8 for groups breast-feeding and control, respectively. The control of phe levels in blood was adequate in the majority of the patients from breast-feeding group. In this group, the average ratio of phe level in blood presented greater number of exams 360 < ì mol/L, and also a lower variability of the results in comparison with control group. The anthropometric evaluation showed that practically all the PKU patients, from both the groups presented the score Z concerning the evaluated indexes in the limits of normality, with significant improvement in the evolution of these indexes. The mean of cephalic perimeter evaluation showed improvement in the evolution, with significant difference between the initial and final measure in both groups. In summary, it is possible to use breast-feeding in the treatment of PKU infants during a period of time relatively long, and, all the advantages of breast-feeding are gotten, with no loss on the control of phe levels in blood or in relation to the patients nutritional condition